-18-6z=6(1+3z)

Simple and best practice solution for -18-6z=6(1+3z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18-6z=6(1+3z) equation:


Simplifying
-18 + -6z = 6(1 + 3z)
-18 + -6z = (1 * 6 + 3z * 6)
-18 + -6z = (6 + 18z)

Solving
-18 + -6z = 6 + 18z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-18z' to each side of the equation.
-18 + -6z + -18z = 6 + 18z + -18z

Combine like terms: -6z + -18z = -24z
-18 + -24z = 6 + 18z + -18z

Combine like terms: 18z + -18z = 0
-18 + -24z = 6 + 0
-18 + -24z = 6

Add '18' to each side of the equation.
-18 + 18 + -24z = 6 + 18

Combine like terms: -18 + 18 = 0
0 + -24z = 6 + 18
-24z = 6 + 18

Combine like terms: 6 + 18 = 24
-24z = 24

Divide each side by '-24'.
z = -1

Simplifying
z = -1

See similar equations:

| 4x-(3x+2)=3x-14 | | 14n+11n+10=85 | | 9x-18x+27=0 | | 5(w+6)=4(w+3) | | 5x+7=31+9x | | 42z^2-zy-y^2= | | 17=6h-6 | | W=XYZfory | | -5x+3(x-1)=-11 | | 4(50-0.5y)+2y=200 | | f(4)=-3-4+7 | | 9x^8-18x^7-27x^6=0 | | (2x+1)(x+2)-(x-1)(3x+1)=1 | | 3k-8k=-12-k | | 7+6h=7+5h+3h+10 | | 5x+4-2x=7x+4 | | 62=9w+20 | | 2k+5k=9 | | 6a(5a)-7a+4a=(9) | | 10q+12=30 | | 16x+4x+1=0 | | f(4x)=-3x+7 | | 4(50+-0.5y)+2y=200 | | 5(3d+4)=2(2d-1) | | 5k/3=20 | | ln(x^2-7)=ln(3-3x) | | 1/2x-14=-13 | | 3k/2=9 | | 9x^2-30x+36=0 | | 12=6m+18 | | -6=8-2n | | 6+14=17 |

Equations solver categories